CELEBRITY ENDORSEMENT AND BUYING BEHAVIOR: A STUDY OF PANJAB UNIVERSITY STUDENTS - Kaur, Supreet; Garg, Ankit (International Journal of Research -GRANTHAALAYAH, 2016)
In present era, there has been a change in consumer’s attitude towards lifestyle. Consumers give importance to brands to ensure better standard of living. Today consumers are not only educated but also selective while purchasing products. Everyday consumers are exposed to number of voices over the radio and TV and images in newspapers, magazines, hoardings, and websites. Therefore, every marketer tries to steal at least fraction of a person’s time to inform him/her of the amazing and different attributes of the product at hand and for this purpose marketers use celebrity endorsement as an effective marketing strategy to fit their products in the minds of consumers. The practice of celebrity endorsements has proliferated over time and perceived as a winning formula for product marketing and brand building. This paper is an effort to analyze the impact of celebrity endorsements on buying behaviour of the college students. Questionnaire survey was used to collect the data by using convenience sampling.